PROTECTION OF OPERATING SYSTEMS AGAINST POSSIBLE THREATS - Єгоров, С. (Proceedings of National Aviation University, 2012)
Efficiency of usage of programs which return OS to an initial state after reboot and select the virtual environment for software start, it has been proved by their usage in Internet cafe and in educational institutions. The organization of protection of OS from hacker attacks and the harmful software difficult enough task. It is connected by it is necessary what to resist to experts who have high qualification and intelligence. Program writers of protection not in a state completely to trace appearance of the new harmful software and hacker attacks. The unique method to resist to all types of threats which influence OS closed source is a tracing and timely setting of appropriate updates for OS, and also timely update of anti-virus bases. If to adhere to all recommendations which are stated in this article it is possible to lower considerably probability of loss of the information from influence of various threats on OS